A Comparative Study of the Effect of Including Full-Fat Tenebrio molitor for Replacing Conventional Ingredients in Practical Diets for Dicentrarchus labrax Juveniles - Sara Flores-Moreno; Francisco Javier Alarcón-López; Antonio J. Coronel-Domínguez; Eugenia Zuasti; Ismael Hachero-Cruzado (Animals)
Tenebrio molitor (TM) meal is a potential alternative ingredient to plant and fishmeal in aquafeeds due to its high protein content, digestibility, and low environmental impact. However, its low n-3 PUFA (EPA and DHA) content represents one of its main limitations. This study evaluated the effects of replacing fishmeal and plant-derived ingredients (plant proteins and soybean oil) with full-fat TM meal on the growth performance and lipid composition of tissues in juvenile European seabass (Dicentrarchus labrax). Four experimental diets, including 5–10% TM for replacing fishmeal and soybean oil (FM5 and FM10) and 10–20% TM for substituting plant protein ingredients and soybean oil (PI10 and PI20), were tested over 49 days against a control diet (CT). Fish fed on PI20 exhibited the highest growth performance (final weight: 49.73 g and SGR: 1.78% day−1) compared to fish fed on FM (final weight: 47.0 g and SGR: 1.62% day−1) and CT (final weight: 48.45 g and SGR: 1.71% day−1). In general, the diets containing TM modulated the lipid profile in fish tissues by reducing the liver lipid content and muscle triglycerides and increasing the n-3/n-6 ratio compared to the CT diet. However, the most effective approach for modulating those parameters seems to be using the TM meal for replacing the plant ingredients instead of substituting fishmeal. Moreover, this feeding strategy, demonstrated to be useful for promoting the growth of fish owing to the use of the TM meal for replacing fishmeal, resulted in a slight reduction in the final weight of the fish.